PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDEN THEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 025 SUNGAI TUNGGAK KECAMATAN KUBU - Gindi Priammono; Zariul Antosa; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The problem in this study is the low IPS student learning outcomes. Thepurpose of this research is to improve learning outcomes IPS Elementary Schoolfifth grade students 25 Tunggak River, the Application Model Type CooperativeStudent Teams Achievement Division (STAD). The hypothesis of this study is thatif applied STAD cooperative learning model, it can improve learning outcomesIPS Elementary School fifth grade students Tunggak River 025. The resultsshowed the activity of teachers in the first cycle showed 60% first meeting, asecond meeting of the first cycle of 70%, the second cycle of the third meeting86.66%, the fourth meeting of Cycle II 86.66%. Activity of teachers in this studyincreased. Student activity first cycle of 60% the first meeting, a second meetingof the first cycle 66.66%, the second cycle of the third meeting of 76.66%, thefourth meeting of Cycle II 83.33%. Activity of students in this study alsoincreased. The results of the initial data menunnjukkan social studies whocompleted only 12 percent of students with 40% who did not complete 18 percentof people with 60%. Students who earn a score above the basic standard minimumcompleteness criteria (KKM) in the first UH students who complete 21 or 70% thepercentage of incomplete 9 people with the percentage of 30%. In the second UHstudents who completed 28 or 93.33% percentage of incomplete 2 people or apercentage of 6.66%. IPS learning outcomes in this study is increased, then theapplication of learning models of type Cooperative Students Teams AchievementDivision (STAD) Social learning results receivedKeywords: Type STAD cooperative, IPS Learning Outcomes